Ethical principles for talent identification in sports from the liberal perspective - Vicar, M.; Moudr, V. (Sport, Ethics and Philosophy, 2020)
Even though talent identification in sport is considered by many to be a positive phenomenon, there are several controversies associated with the issue. This article deals with these disputations from the liberal position placing the individual at the centre of our focus. Talent identification is viewed as an example of Maxwell`s demon. Based on questionable methods, it provides children with unequal opportunities and builds a barrier preventing their involvement in sport and development. Equality, as defined by Rawls` theory of justice, and the child`s right to an open future stipulated by Feinberg, may be easily violated by current practice. Further concerns are connected with placing undue emphasis on effort, limitation of resources, pressure on children to specialise at young age and necessity to undergo the whole process of identification, false positive and negative decisions in talent identification and consequential self-fulfilling prophecies. As a result of these issues, seven principles for talent identification in sport from the defined liberal perspective are formulated.